Assessment of surface microhardness of enamel surface treated with Nano- HAP serum before and after bleaching - Marwa H Abd; Rasha H Jehad; Mahdi Mutahar (Journal of Baghdad College of Dentistry, 2024)
Background: Although bleaching is typically considered a safe procedure, various investigations have found minor negative effects and changes in mineral composition. The aim was to Evaluate and compare the efficacy of using Nanohydroxyapatite serum on surface microhardness of enamel surface before and after bleaching with chemically cured Boost bleaching. Material and methods: ten sound human permanent upper and lower premolar teeth were used and their roots were removed 2 mm apically to the cementoenamel junction, the crowns were sectioned mesiodistally into two halves buccal and lingual/palatal, the buccal surface was further subdivided into two halves. The samples were embeded in an acrylic resin, resulting in 30 specimens divided into 3 groups: Control group: using Boost bleaching and stored in artificial saliva for 14 days, prevention group: nanohydroxyaptite (n-HAP) serum applied 2-3 min once daily  for 10 days followed by bleaching then stored for 14 days in artificial saliva and treatment group: in which bleaching used before nanohydroxyapatite serum and stored in artificial saliva for 14 days. The samples were subjected to a Vickers microhardness test measured at 4 times: base line, after nanohydroxyapatitem, after one day of bleaching and after storage in artificial saliva for 14 days in all groups. The data were analyzed statistically using repeated analysis of variance (ANOVA) test followed by Tukey's test. Results: there was a significant increase in microhardness in the prevention group (p<0.05) while there was no significant difference in microhardness readings in control and treatment groups (p> 0.05). Conclusion: n-HAP may enhance the microhardness of a bleached enamel surface when used as a preventive & treatment measure. Suggested that a higher increase in enamel microhardness occurs when n-HAP is used for 2-3 min once daily for 10 days before bleaching and maintaining this increase even after storage for 14 days in artificial saliva.